The Effect of Felt Pressure and Adhesive Lath Weight on The Physical and Mechanical Properties of The Combination of Petung Bamboo and Sengon Laminated Boards - Febriana Tri Wulandari; Radjali Amin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Sengon wood as a construction material has several weaknesses, namely its specific gravity of 0.33 which is included in the light specific gravity (0.29-0.56) with a strong class III-IV. To increase the strength of sengon wood by making sengon wood into laminated boards combined with bamboo laminates. The aim of this study was to examine the effect of labur weight, compression pressure and their interactions on the physical and mechanical properties of the laminated boards of a combination of sengon wood and petung bamboo and to determine the strength class of the laminated boards based on their physical and mechanical properties. The research method used was the experimental method with a factorial Completely Randomized Design (CRD) experiment with 2 factors with 4 treatments and 3 replications. Based on the results of the study, it can be concluded that labur weight, felt pressure and their interactions have no significant effect on the physical properties of the laminated board combination of sengon wood and petung bamboo while the mechanical properties have a significant effect. All tests of physical and mechanical properties comply with SNI 01-6240-2000 and JAS 234-2007 standards. Based on the results of testing the physical and mechanical properties, the laminated board combination of sengon wood and petung bamboo is included in the strength class III which can be used for protected heavy construction.